The Model of the Meander Delay Systems with Complicated Form of the Taps - Gurskas, A.; Kirvaitis, R.; Martavicius, R. (Elektronika ir Elektrotechnika, 1997)
The mathematical model for automated design and analysis of the meander multitapped delay systems with the complicated form of the taps is proposed. The mathematical model consists of dispersion equation, formulas of connection between amplitude factors and formulas of input impedance of the delay systems. The expressions of “particular” points on the frequency responses of the delay systems are presented. These expressions are indispensable for the preparing of the software for automated design and analysis.